The Effect Of Tax Knowledge, Tax Sanctions On Taxpayer Compliance In Paying Motor Vehicle Tax At PT. Nagase Impor-Expor Indonesia - Hutajulu, Rachel G.; Pangaribuan, Hisar (Universitas Pahlawan Tuanku Tambusai, 2023)
This research was conducted at PT. Nagase Import-Export Indonesia to better understand the impact of tax information and tax sanctions on taxpayer compliance with motor vehicle tax payments. The goal of this quantitative study is to confirm or refute assumptions about the impact of taxpayer awareness and tax penalties on PT. Nagase Import-Export Indonesia's compliance with its motor vehicle tax payment obligations. A survey of 59 taxpayers was used to obtain the data. Multiple linear regression is used to analyze data. Motor vehicle tax compliance turns out to be significantly influenced by taxpayer knowledge variables, tax sanctions, and tax knowledge. Keywords: Tax knowledge, tax sanctions, and taxpayer compliance.